The Effect of Used Form and Level Green Cincau Leaves (Cycleabarbata L. Miers) as Feed Additive on Broiler Performance Production - Muhammad Halim Natsir; Osfar Sjofjan; Muharlien Muharlien (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
The aimed research was to examine the effect of used form and level green cincau leaves (Cycleabarbata L. Miers) as feed additive on broiler performance (feed consumption, body weight gain, feed conversion ratio and income over feed cost). The materials used were 192 Day Old Chicks (DOC) of Lohman MB Platinum with average initial body weight of 37.4±2.87 g, encapsulated or non encapsulated green cincau leaves (Cycleabarbata L. Miers) and encapsulants. Encapsulants that used was the mixture of gum arab-whey (4:1) wich was added BHT 0.06%. Encapsulants that used was 25% of green cincau leaves (Cycleabarbata L. Miers). The method in this experiment was in vivo experiment with Nested Completely Randomized Design with 2 form of green cincau leaves (Cycleabarbata L. Miers) (non encapsulated and encapsulated) and 4 levels of inclusions 0, 0.5, 1.0 and 1.5%, if there were significant effect it would be future tested with Duncan’s Multiple Range Test. The result showed that green cincau leaves (Cycleabarbata L. Miers) in either encapsulated and non encapsulated form didn’t significantly effect (P>0.05) on consumption, feed conversion ratio and IOFC, but it significantly affected (P<0.05) body weight gain and they tended to increase (P<0.01) production index. Increasing levels of green cincau leaves (Cycleabarbata L. Miers) form 0 to 1.5% in encapsulated and non encapsulated form didn’t significantly improve feed conversion ratio, IOFC and production index, thought they tended to increase (P<0.05) feed consumption and they tended to increase (P<0.01) body weight gain. The conclusion of this research was encapsulated better than non encapsulated green cincau leaves (Cycleabarbata L. Miers). The optimal level of feed additive in encapsulated green cincau leaves (Cycleabarbata L. Miers) was 1.0%.